Pemanfaatan Limbah Sampah Plastik Menggunakan Metode Ecobrick di Desa Luwuk Kanan - Ridha Nirmalasari; Ahmad Ari Khomsani; Dhea Nur’aini Rahayu; Lidia Lidia; Maulida Rahayu; M. Rezqi Anwar; Meliyani Syahrudin; Rahmatul Jennah; Salma Syafiyah; Suriadi Suriadi; Yoga Setiawan (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Background: Plastic is a non-organic waste that has many benefits, especially in everyday life, especially sellers in the market in food packaging, basic materials for making automotive components, and can be used as a primary material for making toys. The amount of plastic used by the community and thrown away after use will cause the emergence of waste. This devotion program is intended so that citizens can use waste to produce goods of economic value. Luwuk Kanan village is a village that has a large percentage of the population, from the large number of residents resulting in the emergence of problems regarding waste management, so far the community copes with garbage in the village by burning and not a few who throw it into the katingan river stream, this is what causes river siltation that results in flooding. Based on these problems, Ecobrick can be a solution to reduce and utilize plastic waste into economically valuable products. Method: PAR (Participatory Action Research) is a problem-based devotion that is found and then provides alternative solutions. Results: Utilization of plastic waste in Luwuk Kanan Village with Ecobrik method. Ecobrick is one of the recycling methods, which is a term for plastic bottles filled with non-organic materials until they become very dense and complex. Conclusion: The introduction of ecobric methods can now process waste into materials of economic value and environmentally friendly.